2022-RA-465-ESGO Pelvic exenteration with neurovascular and bony resections for gynaecological tumours: a systematic review. (20th October 2022) - Denys, Andreas; Thielemans, Sofie; Salihi, Rawand; Sys, Gwen; Tummers, Philippe; van Ramshorst, Gabrielle H
Abstract : Introduction/Background: Pelvic exenteration (PE) with neurovascular or bony resections can be curative in gynaecological oncology, but has significant impact on quality of life (QoL) and high morbidity. The primary outcome of this systematic review was the QoL and secondary outcomes included morbidity and mortality after PE with neurovascular or bony resections. Methodology: The protocol was registered in PROSPERO, and included specific search strategies for PubMed, EMBASE, Cochrane Library, Google Scholar, Web of Science and ClinicalTrials.gov. Studies published from 1966 onwards reporting on QoL of patients who underwent PE with neurovascular or bony resections were considered eligible. Study selection, data extraction, rating of evidence (GRADE) and risk of bias (ROBINS-I) were performed independently by two reviewers using Rayyan. Results: Of 341 identified records, 10 studies on 89 patients were included: 1 prospective study, 6 retrospective studies, and 3 case reports. All studies were very low quality with an overall serious risk of bias. The primary tumour was located in the cervix (n=42), uterus (n=22), vulva (n=11), vagina (n=3), ovary (n=3), Gartner duct (n=1) or synchronous tumours (n=3). For 4 patients the primary tumour was not reported. Bony resections included the pubic (n=11) and pelvic bone (n=9), hemipelvectomy (n=7), sacrectomy (n=2) and the transverse process of L5 (n=1). Margins were negative in 69 patients and were not reported for 6 patients. 14 patients had positive margins (R1: n=6; R2: n=3; 'positive': n=5). 30-day mortality was 1, 1% (1/89). 3 studies reported on improved QoL after surgery, of which only one used a validated QoL questionnaire. Most frequently reported complications were infectious. Conclusion: Despite the sparsity of published studies, QoL seems to be improved after PE with neurovascular or bony resections in a highly selected patient group. There is a need for collecting QoL outcomes in a validated and uniform manner.